2015
DOI: 10.1017/s1460396915000102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an inter-centre, web-based radiation oncology peer-review case conference

Abstract: PurposePeer-review programmes in radiation oncology are used to facilitate the process and evaluation of clinical decision-making. However, web-based peer-review methods are still uncommon. This study analysed an inter-centre, web-based peer-review case conference as a method of facilitating the decision-making process in radiation oncology.MethodologyA benchmark form was designed based on the American Society for Radiation Oncology targets for radiation oncology peer review. This was used for evaluating the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Six types of team collaboration in oncology care were distinguished (table 1): (1) Expert MDTM-national: provides expertise and experience on rare tumours nationally (17 studies) 18-34 ; (2) Expert MDTM-International: provides international expertise and experience on rare tumours (5 studies) [35][36][37][38][39] ; (3) Expert Consultation: physicians caring for complex patients seeking a consultation with experts (11 studies) [40][41][42][43][44][45][46][47][48][49][50] ; (4) Consultation Specialist-Nurse: nurses consulting with palliative treatment specialists in specialised palliative care units or hospices (4 studies) [51][52][53][54] ; (5) MDT-Equal: involving more or less equal MDTs that use each other for a 'fresh look' to optimise the diagnostic and treatment plans for complex cases (5 studies) [55][56][57][58][59] ; and (6) MDTM-Collaborate: MDTs collaborating to form one MDTM (8 studies) [60][61][62][63][64][65][66][67] (online supplemental file 5).…”
Section: Thematic Analysis and Synthesis Of Subsetsmentioning
confidence: 99%
“…Six types of team collaboration in oncology care were distinguished (table 1): (1) Expert MDTM-national: provides expertise and experience on rare tumours nationally (17 studies) 18-34 ; (2) Expert MDTM-International: provides international expertise and experience on rare tumours (5 studies) [35][36][37][38][39] ; (3) Expert Consultation: physicians caring for complex patients seeking a consultation with experts (11 studies) [40][41][42][43][44][45][46][47][48][49][50] ; (4) Consultation Specialist-Nurse: nurses consulting with palliative treatment specialists in specialised palliative care units or hospices (4 studies) [51][52][53][54] ; (5) MDT-Equal: involving more or less equal MDTs that use each other for a 'fresh look' to optimise the diagnostic and treatment plans for complex cases (5 studies) [55][56][57][58][59] ; and (6) MDTM-Collaborate: MDTs collaborating to form one MDTM (8 studies) [60][61][62][63][64][65][66][67] (online supplemental file 5).…”
Section: Thematic Analysis and Synthesis Of Subsetsmentioning
confidence: 99%
“…Crispen et al 11 analyzed the use of web-based peer review in three Caribbean radiation oncology centers. The review noted the positive attitude of users to introducing web-based peer review to small or isolated radiotherapy centers, and recommended that identifying the appropriate technology to achieve this could result in the successful implementation of peer review.…”
Section: Introductionmentioning
confidence: 99%
“…The MDTMs held by UMC and by the secondary hospital have been merged and using video-conferencing to reduce the number of MDTMs and decrease throughput times. Research on care pathway management in Scotland has shown that throughput time measurements on several levels should be taken into account to improve coordination in a region [46], and this is reflected in our recommendations below.…”
Section: Quantitative Resultsmentioning
confidence: 97%
“…A limitation of this study is the lack of generally accepted indicators for care pathway management and definitions of those indicators that do exist [46] [57] [63]. We modified Dutch SONCOS standardised indicators to evaluate the reorganisation of the care pathways in order to be comparable to the indicators used in earlier research on the care pathway of head-andneck cancer patients [31].…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation